Prescrições de práticas professorais de educação infantil no município de São Paulo - Aleixo, Camila Rosa dos Santos (2019)
This research is located in the Master Program in Management and Educational Practices (Progepe) of the University Nove de Julho (Uninove), specifically in the line of research and intervention in educational management (Lipiges). The object of this study was proposed the teacher of early childhood education of the municipal school of São Paulo outlined in documents produced by the Municipal Secretariat of Education since the mid- 2000s. It is worth mentioning that from this object emerged the following concerns that guided and motivated The development of this research: What documents are these? What is the tone, scope, purpose, language and content of these documents? In this context, what can we understand as prescriptions for teaching practices? What teachers do the documents propose, draw and format? What is the teacher's role in carrying out the secretary's proposals according to the documents? With these research questions outlined, it was delimited, as a general objective, to analyze the prescriptions of the documents for the practices of teachers of kindergarten of the municipal school of São Paulo, and to draw a profile of the teacher conformed in these documents. As a specific objective, it was estimated: to describe and analyze the SME documents cited here, trying to capture what is normalized regarding teachers; establish analytical categories as to what they claim about the teacher; to compare the statements of the documents with what the legal provisions on early childhood education say regarding teaching performance: to verify the contact points of the official discourse present in the documents with what the literature says about the early childhood teacher. From these objectives, the research was developed according to a qualitative approach, which unfolds in three different possibilities in the accomplishment of a research: the documentary research, the case study and the ethnography. The universe of research was defined by the official documents of the Municipal Secretariat of Education: Childhood Curriculum Guidelines: Learning Expectations and Didactic Guidelines for Early Childhood Education (2007); Assessment in Early Childhood Education: Improving Looks (2013); Integrating Curriculum of São Paulo's childhood (2015); Quality standards in early childhood education Paulistana (2015); Quality indicators of São Paulo kindergarten (2016). Thus the research was developed dialoguing with the theoretical references, such as: Kuhlmann (2001), Rosemberg (1995) and Vercelli (2015) when dealing with early childhood education, Gatti (2009), Nóvoa (1995) and Garcia (1999) on the theme. teacher education, and Bardin (1995) and Bioto-Cavalcanti (2013) in document analysis. As the main result of this study provided an understanding of the scope in which prescriptions of practices are revealed in early childhood education, trends were found that shape the preschool teacher as an executor of prescriptions contained in the documents of the Municipal Secretariat of Education of São Paulo.